2008
DOI: 10.1111/j.1399-0012.2008.00815.x
|View full text |Cite
|
Sign up to set email alerts
|

CD25, CD28 and CD38 expression in peripheral blood lymphocytes as a tool to predict acute rejection after liver transplantation

Abstract: The evaluation of CD28 and CD38 expression in peripheral blood lymphocytes is a simple marker that could be used routinely in clinical practice to assess the level of immunosuppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 30 publications
1
26
0
1
Order By: Relevance
“…Most recent report, Boleslawski et al reported that mean frequencies of CD28 and CD38 expressing T cells were significantly higher in patients with acute rejection, but there was no difference between patients with or without infection in 52 recipients. 8) Although this method may be effective for the prevention of acute rejection, it can't predict bacterial and cytomegalovirus infection occurred by overimmunosuppression. The mean values of IC 50 were significantly different among the subjects (pϽ0.005; with one-way ANOVA).…”
Section: Discussionmentioning
confidence: 99%
“…Most recent report, Boleslawski et al reported that mean frequencies of CD28 and CD38 expressing T cells were significantly higher in patients with acute rejection, but there was no difference between patients with or without infection in 52 recipients. 8) Although this method may be effective for the prevention of acute rejection, it can't predict bacterial and cytomegalovirus infection occurred by overimmunosuppression. The mean values of IC 50 were significantly different among the subjects (pϽ0.005; with one-way ANOVA).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these were associated with the occurrence of acute rejection, particularly during the early phase after transplantation [8,9,[39][40][41][42]. Data regarding CD152 are somewhat…”
Section: Other Surface Moleculesmentioning
confidence: 96%
“…Boleslawski et al reported an association between a decreased level of CD28 expression on CD8 þ cells and malignancies in long-term liver transplant patients, as well as an association between increased expression and rejection [84,85]. So far, no standardization of assay protocols has been achieved and no sound data from larger clinical trials have been published.…”
Section: T Cell Activation Surface Markersmentioning
confidence: 96%